EXTRAGENITAL TRANSMISSIBLE VENEREAL TUMOR: RETROSPECTIVE STUDY OF 11 CASES - Grandez R., Ricardo (2011)
A medical follow-up on 11 patients with clinical signs compatible with extra-genital canine venereal transmissible tumor was conducted from June 2003 to August 2009. The canines were evaluated and further medical procedures such as radiographies, ultrasounds, cytology and histopathology were performed to confirm the diagnosis. The nasal tumor was the most common presentation (9/11) and unilateral epistaxis was the most common clinical sign (7). Only one case of bilateral epistaxis was observed. Bloody discharge was the only clinical sign observed in cases where the lesion was located in the uterine stump (1) or anus (1). The clinical signs lasted in average 2.8 months (0.5-12 months). The ultrasound and radiographic procedures were helpful in determining the presentation, location and size of the lesions; the cytology and histopathology showed to be suitable clinical procedures to determine the final diagnosis; and treatment with vincristina sulfate, used for 6.5 weeks (4 to 9 weeks) proved to be effective in all cases as imagenological alterations decreased or disappeared.